Balancing sensory inputs: somatosensory reweighting from proprioception to tactile sensation in maintaining postural stability among older adults with sensory deficits - Liu, Ziyin; Wang, Qi; Sun, Wei; Song, Qipeng (Frontiers in Public Health, 2023)
Background: Sensory deficits increase the risk of falls among older adults. The purpose of this study was to investigate the relationship of lower extremity muscle strength, proprioception, and tactile sensation to postural stability among older adults with and without sensory deficits, to understand the contribution of each factor to postural stability, and to explore sensory reweighting in the two populations. Methods: A total of one hundred and three participants were recruited and divided into two older adults groups with- (female = 24, male = 26, age = 69.1± 3.15 years, height = 162.72±6.94 cm, body mass = 64.05 ±9.82 kg) and without- sensory deficits (female = 26, male = 27, age = 70.02± 4.9 years, height = 163.76 ±7.60 cm, body mass = 65.83±10.31 kg), based on whether the position of the foot soles of the 5.07 Semmes-Weinstein monofilament could be detected. Their Berg Balance Scale (BBS), lower extremity muscle strength, proprioception, and tactile sensation were tested and compared between the two groups. Pearson or Spearman correlations were used to explore the relationships between the BBS and each variable. Factor analysis and multivariate linear regression were used to verify the degrees of correlation between the generated factors and the postural stability. Results: Less BBS (p=0.003, η2=0.088) scores and higher proprioception thresholds (Knee flexion: p=0.015, η2=0.059; Knee extension: p=0.011, η2=0.065; Ankle plantarflexion: p=0.006, η2=0.075; Ankle dorsiflexion: p=0.001, η2=0.106) were detected among older adults with sensory deficits compared to those without sensory deficits. Lower extremity muscle strength (Ankle plantarflexion: r=0.342, p=0.002; Hip abduction: r=0.303, p=0.041) and proprioception (Knee flexion: r=-0.419, p=0.004; Knee extension: r=-0.292, p=0.049; Ankle plantarflexion: r=-0.450, p=0.002; Ankle dorsiflexion: r=-0.441, p=0.002) were correlated with BBS among older adults without sensory deficits, while strength (Ankle plantarflexion: r=0.501, p<0.001; Hip abduction: r=0.302, p=0.041) and tactile sensation (Great toe: r=-0.388, p=0.008; 5th Metatarsal: r=-0.301, p=0.042) were correlated with BBS among older adults with sensory deficits. Conclusion: Older adults with sensory deficits have poorer proprioception and postural stability; Somatosensory reweighting occurs from proprioception to tactile sensation among older adults with sensory deficits in maintaining postural stability.maintaining postural stability.